Evaluation of a commercial SD dengue virus NS1 antigen capture enzyme-linked immunosorbent assay kit for early diagnosis of dengue virus infection. - Wang, S.M.; Sekaran, S.D. (American Society for Microbiology, 2010)
Early definitive diagnosis of dengue virus infection may help in the timely management of dengue virus infection. We evaluated the Standard Diagnostics (SD, South Korea) dengue virus nonstructural protein NS1 antigen enzyme-linked immunosorbent assay (SD dengue NS1 Ag ELISA) for the detection of dengue virus NS1 antigen in patients' sera, using a total of 399 serum samples in a comparison with real-time reverse transcription (RT)-PCR, an in-house IgM capture (MAC)-ELISA, and a hemagglutination inhibition (HI) assay. Of the 320 dengue sera, 205 (64%) tested positive for NS1 antigen compared to 300 (93.75%) by either MAC-ELISA or RT-PCR, 161 (50.31%) by RT-PCR, and 226 (70.36%) by MAC-ELISA only. The assay was able to detect NS1 antigen in convalescent-phase sera until day 14 of infection. The NS1 detection rate is inversely proportional while the IgM detection rate is directly proportional to the presence of IgG antibodies. The overall sensitivity and specificity of the SD dengue NS1 Ag ELISA in the detection of "confirmed dengue virus" sera are 76.76% and 98.31%, respectively. This suggests that the SD kit is highly specific and sensitive for the detection of NS1 antigen. However, caution is needed when the kit is used as a single assay, as detection in samples that contained the virus was only about 81.97%. Combining this assay with an IgM and/or IgG assay will increase the sensitivity of detection, especially in areas with a higher prevalence of secondary dengue virus infections.